Trinidad and Tobago : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper analyzes the energy sector and labor market developments in Trinidad and Tobago. It discusses monetary and exchange rate policy and describes the institutional setting and economic structure within which monetary and exchange rate policy is conducted. The framework under which monetary policy is formulated and implemented is outlined. The paper also reviews the evolution of monetary and exchange rate policies, and presents some comments on the effectiveness of monetary and exchange rate policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet